Effects of single and simultaneous application of the parasitoid, Lysiphlebus fabarum and the ladybird beetle, Hippodamia variegata on control of Aphis gossypii on cucumber - Z. Mohammadi; A. Rasekh; M. Esfandiari; J. P. Michaud; F. Kocheili (گیاه‌پزشکی, 2019)
Background and objectives The cotton aphid, Aphis gossypii, is an important pest on greenhouse crops such as the cucumber. Natural enemies have often been used successfully to control greenhouse pests. Among different pests, aphids because of their high reproductive rate are particularly difficult to control biologically. Materials and Methods In this study, the effects of separate and simultaneous application of the parasitoid wasp Lysiphlebus fabarum and the predator ladybird beetle Hippodamia variegata were studied to control A. gossypii on cucumber as an integrated pest management program. The replicates (n= 10) in all treatments included 10 cucumber plants in separate pots and were infected with five winged A. gossypii placed in a cage with a banker plant system of Vicia fabae-Aphis fabae. With the introduction of mummified aphids on a bean shoot (every two days), a pair of male and female adult ladybird beetles (every three days) or simultaneous application of both biocontrol agents, the numbers of aphids were counted in the three treatments. Results The results revealed that the parasitoid wasp L. fabarum alone was unable to control A. gossypii, but H. variegata performed better. The best performance was observed for simultaneous application of both biocontrol agents. Moreover, in the combined agents’ treatment, the number of A. gossypii on the both lower and upper cucumber leaves was not significantly different compare to other treatments that biological agentswere used seperatly. The number of mummified aphids did not differ between treatments at the end of the experiments. This is indicative of the tendency for ladybird beetles to feed on different growth stages of non-parasitized aphids compare to parasitized aphids containing immature stages of L. fabarum. Discussion The results indicate thatthe simultaneous application of both biocontrol agents is effective for the control of A. gossypii, although more research under greenhouse condition is needed.